Linear Array Thinning Using JAYA-Iterative Fourier Technique - Yang, Xin; Wan, Mi; Zhao, Yanwen; Yang, Deqiang (2023 International Applied Computational Electromagnetics Society Symposium (ACES-China), 2023)
In this paper, a hybrid algorithm, namely JAYA-iterative Fourier technique (JAYA-IFT), is presented for linear array thinning. This algorithm is based on the combination of two methods, JAYA and the iterative Fourier technique (IFT). JAYA serves as the primary framework of the algorithm while IFT is utilized to refine the best solution in each iteration. By this means, the IFT is incorporated into the algorithm as prior knowledge to facilitate and improve convergence. Two linear array syntheses were carried out using the proposed JAYA-IFT method. Numerical results were provided to verify the effectiveness of the proposed method.